"If I was not here I do not know where I would be" - Perspectives on the Potential of Second-level schools to Positively Affect Student Development in Urban Areas Characterised by Socioeconomic and Educational Disadvantage in the Republic of Ireland and State of Massachusetts - O'MALLEY, JOHN BRIAN (Trinity College Dublin. School of Education. Discipline of Education, 2018)
This study is a contribution to the field of Educational Effectiveness Research (EER). Its uniqueness lays in the use of an international comparative approach and student perspective to investigation the aspects of second-level schools to impact the academic, self-esteem and civic responsibility of students in the Republic of Ireland (ROI) and State of Massachusetts (MA). Recognising the multi-faceted nature of human development, Bronfenbrenner?s (2005) Bioecological Theory of Human Development is used as the Conceptual Framework to guide the construction, application and analysis of the dissertation. The focus of the study?s literature review was framed by the research question. Chapter 2 provides an overview of the structure of the second-level education system in each of the contexts. Additionally, it offers a discussion on current policy in each of the contexts around the academic, self-esteem and civic responsibility development of students from urban, disadvantaged communities. Chapter 3 then outlines the conceptual framework for this study, through explaining the Bioecological Theory of Human Development. Finally, Chapter 4 provides a discussion of EER literature and the aspects of second-level schools found to impact the academic, self-esteem and civic responsibility development of student. In relation to the primary research study, the two contexts chosen to participate in the primary research study were the Republic of Ireland (ROI) and the State of Massachusetts (MA). Using ROI and MA as the research locations, a study with the following elements was developed: A focus on six participating schools all located in urban areas characterised by socioeconomic and educational disadvantage, A research period of two-years, A focus on one student cohort over the two-years in each case study school using questionnaires to be completed by the entire cohort at the beginning and end of the case study and three interviews to be conducted with six students from each case study school, additional data was to be collected via interviews conducted with the principal and teacher from each of the participating case study schools. As a result of this research, and supported by the literature, it was concluded that the school-based elements that should be encouraged to impact the academic, self-esteem and civic responsibility development of students are: (a) Having teachers that had well developed affective skills (support and caring), high expectations levels of their students and employed effective teaching strategies; (b) a transformative school culture; (c) providing new experiences and opportunities for students to broaden their horizon.
APPROVED